An Improved Power Controller For A Single Phase Grid Connected Inverter With Root Locus Analysis - Élcio Precioso de Paiva; João Batista Vieira Jr.; Luís Carlos de Freitas; Valdeir José Farias; Ernane Antônio Alves Coelho (Eletrônica de Potência)
This paper presents an improved controller for a single-phase inverter connected to the grid, which is based on frequency and voltage droops. A new feedback loop is introduced to increase the system damping. The small signal analysis and root locus plots are presented in order to show the connections between the feedback loop gains and the behavior of the system. Simulation results corresponding to the numerical solution of the nonlinear system equations are presented to validate the small signal analysis. A description of a laboratory prototype and the respective experimental results are also presented to confirm the theoretical analysis.